2012
DOI: 10.1016/j.jval.2012.08.1913
|View full text |Cite
|
Sign up to set email alerts
|

PIH41 Long-Term Fiscal Implications of Funding Assissted Reproductive Therapies: Review of the Literature

Abstract: dex scores have been slightly increased from 0.94 to 0.96 during 2007-2010. Male adults had higher EQ-5D index scores than female (0.96 vs. 0.92). Elderly (ageՆ60) had significantly lower EQ-5D index scores (score ranges: 0.02 to 0.11) than young adult (ageϭ19-29) after adjusting for other variables. EQ-5D index scores were significantly reduced by stroke (reduced by -0.10), arthritis (reduced by -0.05), cardiovascular disease (reduced by -0.04), and diabetes (reduced by -0.02). CONCLUSIONS: QOL in South Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Previous studies have shown that, even under the most optimistic projections, a declining birth rate combined with an ageing population might result in fiscal imbalances that can only be mitigated through spending cuts or tax increases ( IMW Instituto Max Weber, 2012 , MESS Ministry of Employment, 2006 , National Research Council, 2012 , Pérez-Camarero et al, 2012 ). A higher birth rate would contribute to a medium-term increase in the taxpaying population and offset the imbalances caused by the growth of the ageing population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that, even under the most optimistic projections, a declining birth rate combined with an ageing population might result in fiscal imbalances that can only be mitigated through spending cuts or tax increases ( IMW Instituto Max Weber, 2012 , MESS Ministry of Employment, 2006 , National Research Council, 2012 , Pérez-Camarero et al, 2012 ). A higher birth rate would contribute to a medium-term increase in the taxpaying population and offset the imbalances caused by the growth of the ageing population.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, public funding of assisted reproductive treatment could have a positive effect not only on mitigating the excess demand and the current inequity in access to healthcare services, but it could help restore replacement rates and improve fiscal stability ( Pérez-Camarero et al, 2012 ). Indeed, beyond the obvious benefit of assisted reprodution allowing a couple to conceive, generally improving their quality of life, it could produce a social benefit that goes far beyond the direct individual benefit, because each individual conceived contributes a tax flow to society, especially during his/her working life.…”
Section: Introductionmentioning
confidence: 99%
“…It has been calculated that each healthy IVFconceived child becomes a net contributor to society after age 36 to 37 (compared with age 34 for naturally conceived children). 8 Funding IVF would also bring women to treatment sooner, when their chances of conception are better. As women enter their late thirties, the gain in pregnancy rates with treatment over expectant management in many cases is marginal, and the expense of treatment becomes significant.…”
mentioning
confidence: 99%
“…Ne perdons pas de vue qu'un enfant en santé constitue un futur contribuable. On a calculé que chaque enfant en santé issu de la FIV offre une contribution nette à la société après l'âge de 36-37 ans (par comparaison avec 34 ans, pour ce qui est des enfants issus d'une conception naturelle) 8 .…”
unclassified